Kyphoplasty in the treatment of occult and non-occult metastatic vertebral tumors. Issue 25 (19th June 2020) - He, Shuangjun; Zhou, Zhangzhe; Zhang, Changhao; Lv, Nanning; Qian, Zhonglai; Sun, Zhiyong
Abstract : Abstract: To compare the efficacy and safety of kyphoplasty (KP) in the treatment of occult metastatic vertebral tumors (OMVT) and non-occult metastatic vertebral tumors (MVT). From January 2013 to December 2017, 65 cases of occult metastatic vertebral tumors and 82 cases of metastatic vertebral tumors were selected and divided into 2 groups. After KP, they were followed up by a year of outpatient visits and telephone calls. The visual analogue scale (VAS) and Oswestry disability index (ODI) scores, the amount of bone cement injected, the change of vertebral height and the incidence of complications were recorded, compared and analyzed by SPSS software. t test was used to compare the differences between the same group of patients at different times and between the 2 groups of patients. In the OMVT group, the operation time was 24.52 ± 4.24 minutes, the fluoroscopy time was 10.18 ± 1.53 minutes and the volume of bone cement was 3.62 ± 0.93 ml. The VAS score decreased from 7.26 ± 01.08 preoperatively to 2.77 ± 0.93 postoperatively ( P  < .01). The ODI score decreased from 64.89 ± 9.05 preoperatively to 25.82 ± 4.63 postoperatively ( P  < .01). In the MVT group, the operation time was 26.63 ± 4.61 minutes, the fluoroscopy time was 11.04 ± 2.15 minutes and the volume of bone cement was 4.09 ± 1.10 ml. The VAS score decreased from 7.73 ± 0.94 preoperatively to 3.22 ± 0.80 postoperatively ( P  < .01). The ODI score decreased from 69.20 ± 7.14 preoperatively to 28.02 ± 4.40 postoperatively ( P  < .01). The vertebral height of MVT patients was significantly improved after operation ( P  < .01), but there was no difference in OMVT patients ( P  > .05). Occult metastatic vertebral tumors can be detected by Magnetic Resonance Imaging (MRI), and KP may be more effective and safer in the treatment of OMVT. Abstract : Supplemental Digital Content is available in the text